Respostas
respondido por:
1
Olá boa tarde!
Sistema de equações:
2x + y = - 3
x + y = - 1
Irei resolver pelo método da adição:
Observe:
2x + y = - 3
x + y = - 1 . (-1)
____________
2x + y = - 3
- x - y = 1
__________
x = - 2
Então:
x + y = - 1
- 2 + y = - 1
y = - 1 + 2
y = 1
S = {- 2 e 1}
x = - 2 e y = 1
****Bons Estudos****
Sistema de equações:
2x + y = - 3
x + y = - 1
Irei resolver pelo método da adição:
Observe:
2x + y = - 3
x + y = - 1 . (-1)
____________
2x + y = - 3
- x - y = 1
__________
x = - 2
Então:
x + y = - 1
- 2 + y = - 1
y = - 1 + 2
y = 1
S = {- 2 e 1}
x = - 2 e y = 1
****Bons Estudos****
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás